A girl with synostotic plagiocephaly: unfolding as rare case - Arya, Preeti; Bhadra, Sanket; Jassal, Monica; Rathaur , Vyas K. (International Journal of Contemporary Pediatrics, 2024)
Dysmorphic head shape can be a presenting complaint of craniosynostosis which needs to be investigated in detail for any genetic or syndromic associations. Many genetic mutations have been associated with craniosynostosis but ERF gene mutation has been found to be very rare. Here, we have discussed about an 8 years old girl who presented with dysmorphic head shape. She had crouzoid features like exorbitism, malar hypoplasia with copper beaten skull appearance and pansynostosis on CT Head but genetic evaluation revealed ERF gene mutation suggestive of craniosynostosis 4. She had short stature which was the unique association with it. Thus, high index of suspicion should be kept for craniosynostosis 4 when phenotypic features are suggestive of crouzon syndrome as crouzon syndrome can phenotypically mimic craniosynostosis with ERF gene mutation and genetic analysis should be done to look for alternate cause of craniosynostosis; especially to look for ERF gene mutation.